PENGARUH PENGGUNAAN MEDIA BAHAN ALAM LOKAL TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA 5-6 TAHUN - Hasanah, Nurul; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of local natural media media on fine motor development of children aged 5-6 years in PAUD Taman Ceria, Sasan Village. The method used is an experimental method with one-group design, pretest-posttest data with quantitative form. Subjects were 18 children aged 5-6 years, consisting of 9 girls and 9 boys. Sampling uses saturated samples in which the number of samples is less than 50, with data collection techniques using observation. Data collection techniques such as data processing and data presentation, testing data using statistical tests. The results of the data presentation show that there is an increase in fine motor using local natural media, in the form of rubber leaves, rubber seeds, and palm leaves. Then based on calculations done with SPSS assisted version 20, it is known that the t value in the SPSS output after data processing (paired sample t) is obtained with a Sig (2-tailed) value of 0.005 smaller than (0.05) while from the calculated results, obtained value (3,267)> from t table (2,1098). Sig value 2 tailed <0.05 and t arithmetic> T table then Ha is accepted and Ho is rejected. So the results of the study showed that natural media is very influential in improving fine motor development in children aged 5-6 years in PAUD Taman Ceria, Sasan Village.Keywords: Ages 5-6 Years, Fine Motor Development, Local Natural Media.